USP30: Structure, Emerging Physiological Role, and Target Inhibition - Wang, Feng; Gao, Yu; Zhou, Lihui; Chen, Junhao; Xie, Zhiyan; Ye, Zifan; Wang, Yanfeng (Frontiers in Pharmacology, 2022)
Ubiquitin-specific protease 30 (USP30) is a deubiquitinating enzyme (DUB) belonging to the USP subfamily, which was found localized in the mitochondrial outer membrane and peroxisomes owing to its unique transmembrane domain. Structural study revealed that USP30 employed a unique catalytic triad and molecular architecture to preferentially cleave the Lys6 linked ubiquitin chains. USP30 plays an essential role in several cellular events, such as the PINK1/Parkin-mediated mitophagy, pexophagy, BAX/BAK-dependent apoptosis, and IKKβ–USP30–ACLY-regulated lipogenesis/tumorigenesis, and is tightly regulated by post-translational modification including phosphorylation and mono-ubiquitination. Dysregulation of USP30 is associated with a range of physiological disorders, such as neurodegenerative disease, hepatocellular carcinoma, pulmonary disorders, and peroxisome biogenesis disorders. Nowadays, scientists and many biopharmaceutical companies are making much effort to explore USP30 inhibitors including natural compounds, phenylalanine derivatives, N-cyano pyrrolidines, benzosulphonamide, and other compounds. For the treatment of pulmonary disorders, the study in Mission Therapeutics of USP30 inhibitor is already in the pre-clinical stage. In this review, we will summarize the current knowledge of the structure, regulation, emerging physiological role, and target inhibition of USP30, hoping to prompt further investigation and understanding of it.